MODERN APPROACHES TO THE STUDY OF THE NATIONAL AND CULTURAL SPECIFICS OF GERMAN PHRASEOLOGICAL UNITS - Tilovatkhon Khamidova Rakhmatjonovna (Western European Studies, 2024)
This article talks about modern approaches to the study of national-cultural features of German phraseological units, the scientific works and opinions of scientists in this regard, as well as a comparative analysis of some phraseological units with a phytonym component in German and Uzbek
Keywords: phraseological units; phraseological composition; contrasting approach